The University of Costa Rica (UCR) geological congress, 2017-2023 - Mora, Mauricio M. (2024)
Scientific congresses are events to share and submit research results to the scrutiny and debate of the scientific community, which increases the quality of research and promotes the generation of knowledge, innovation and collaboration among peers. The UCR Geological Congress was born from the necessity of having a university forum to disseminate, in a public and open way, the geoscientific research carried out by the professors and students of the geological community of the University of Costa Rica, and at the same time to be an educational space for the students to develop their communication skills. More recently it was opened to the extra-university geological community, in order to promote the interrelation of the academy with the private sector and other public sector institutions. This paper synthesizes the origin and evolution of the UCR Geological Congress from 2017 to 2023, with the aim of leaving its imprint in the university’s historical memory and constituting an input that contributes to the evaluation of the programmatic orientation of geology at the University of Costa Rica. The UCR Geological Congress could be, perhaps, the seed that will encourage the continuity of national geological congresses in the future.